The uninsured in America 1996-2000 - Rhoades, Jeffrey A.; Cohen, Joel W.; Vistnes, Jessica P. (Rockville, 2002)
The Medical Expenditure Panel Survey (MEPS), a household survey that is conducted annually, provides critical data for evaluating trends in the health insurance status of the population. This chartbook presents data from the first year of the survey, 1996, through 2000.